1983
DOI: 10.1182/blood.v62.2.286.286
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-thalassemia is related to prolonged survival in sickle cell anemia

Abstract: We have determined the frequency of deletional alpha-thalassemia in black populations in the USA and Africa that harbor sickle cell anemia. In normals, the frequency of the chromosome bearing a deletion of one of the two normal alpha gene loci, designated (-alpha), ranged from 0.12 to 0.16, and in sickle trait subjects, the frequency ranged from 0.18 to 0.20. By contrast, in sickle cell anemia subjects, the frequency was significantly greater and ranged from 0.22 to 0.33. Analysis demonstrated that the greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
2
4

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(13 citation statements)
references
References 0 publications
0
7
2
4
Order By: Relevance
“…Moreover, 76% of the patients had four ␣-genes (␣␣/␣␣ genotype). The ␣-gene distribution in our pediatric patients with stroke is different than that reported in African Americans with SS at large where the prevalence of ␣␣/␣␣ genotype is about 65%, the −␣/␣␣ genotype about 30%, the −␣/−␣ genotype about 5%, and the genotype with five or more ␣-genes is <2% [8,[13][14][15]. Thus ␣-gene deletion appears to be protective against CVA in children with SS.…”
Section: Discussioncontrasting
confidence: 78%
“…Moreover, 76% of the patients had four ␣-genes (␣␣/␣␣ genotype). The ␣-gene distribution in our pediatric patients with stroke is different than that reported in African Americans with SS at large where the prevalence of ␣␣/␣␣ genotype is about 65%, the −␣/␣␣ genotype about 30%, the −␣/−␣ genotype about 5%, and the genotype with five or more ␣-genes is <2% [8,[13][14][15]. Thus ␣-gene deletion appears to be protective against CVA in children with SS.…”
Section: Discussioncontrasting
confidence: 78%
“…Complications such as leg ulcers, renal pathology, and strokes are fewer, but the frequency of other complications, e.g., osteonecrosis and retinopathy, may be increased (22)(23)(24)(25). Overall survival may also be enhanced (23,26). The present study is probably the first to recognize an association of a-thal trait with preserved splenic function in SS patients with elevated HbF levels.…”
Section: Discussionmentioning
confidence: 53%
“…It decreases the rate of hemolysis by decreasing the MCHC, thereby resulting in higher Hb, Hct, and RBC values (21). Complications such as leg ulcers, renal pathology, and strokes are fewer, but the frequency of other complications, e.g., osteonecrosis and retinopathy, may be increased (22)(23)(24)(25). Overall survival may also be enhanced (23,26).…”
Section: Discussionmentioning
confidence: 99%
“…The other factor which affects clinical severity of sickle cell anemia is the coinheritance of a-thalassemia (Embury et al, 1982;Higgs et al, 1982;Mears et al, 1983). We have recently demonstrated that 22% of Brazilian sickle cell anemia patients have a deletion type a-thalassemia (Costa et al, 19891, a frequency similar to that observed in the USA and Jamaica (Dozy et al, 1979;Higgs et al, 1980).…”
Section: Studies Bymentioning
confidence: 84%